Building a Collaborative Editorial Workbench for Legal Texts with Complex Structures - Nils Geißler; Daniela Schulz (Journal of the Text Encoding Initiative)
This paper presents the work undertaken by the Capitularia project to integrate a collaborative editorial workbench into the open-source content management system (CMS) WordPress. It introduces the reasons for selecting WordPress as the project’s CMS, the workflows established (including a sophisticated XSL-scripting pipeline), as well as three plug-ins created to integrate certain functionalities. The Cap-X2WP plug-in facilitates XSL transformations of XML files to HTML directly within the WordPress framework. The Cap-PaGer plug-in is used to generate WordPress pages automatically based on the XML files located in specific folders on the server. Their publication status can be administered via a special interface added to the general WordPress dashboard at a moment’s notice. Whereas the aforementioned plug-ins facilitate the daily work of the staff members in the general management and enhancement of the project’s website, the Cap-Coll plug-in eases the specific editorial task of collating texts by including the CollateX algorithms in a WordPress plug-in. The report concludes with a brief perspective on the possibilities for further developments.